2023
DOI: 10.3389/fped.2023.1143741
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Joint diagnosis and treatment of intrathoracic gastric duplication with a gastric communication in a child by laparoscopy and gastroscopy

Abstract: Intrathoracic gastric duplication has rarely been reported. A 5-year-old child with gastric duplication located in the left thorax was diagnosed and treated successfully using laparoscopy combined with gastroscopy. Preoperative computed tomography, upper gastrointestinal contrast study, ultrasound, and other imaging methods were insufficient for accurate diagnosis in this case. Laparoscopy combined with gastroscopy is more suitable for the diagnosis and treatment of gastric duplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…With the promotion and maturity of endoscopic minimally invasive technology, many experts at home and abroad have reported the promotion of minimally invasive surgery, namely, laparoscopic resection of gastric duplication. 5 , 22 Krishna Kumar et al 23 reported on a 10-month-old female infant who was diagnosed with nonbiliary vomiting before surgery. Surgeons performed traditional open surgery to remove the 8*6 cm cyst located on the greater curvature of the stomach.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the promotion and maturity of endoscopic minimally invasive technology, many experts at home and abroad have reported the promotion of minimally invasive surgery, namely, laparoscopic resection of gastric duplication. 5 , 22 Krishna Kumar et al 23 reported on a 10-month-old female infant who was diagnosed with nonbiliary vomiting before surgery. Surgeons performed traditional open surgery to remove the 8*6 cm cyst located on the greater curvature of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Before surgery, if it is difficult to remove the top of the cyst or peel off the cyst under gastroscopy or if there is perforation or vascular damage during the surgery, double endoscopy preparation can also be carried out through endoscopy in a timely manner to ensure surgical safety. 5 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations